Solar Panels for Low Power Energy Harvesting - Núñez, Maritza (2023)
Solar panels are widely used nowadays to capture solar radiation and generate voltage, so they are being used for Energy Harvesting applications. The present work carries out the study of low power solar panels for energy storage applications, together with the DC-DC conversion and storage stage. The methodology carried out has been the design, simulation, fabrication and characterization of the elements that form the system. The elements that make up the system are 4 solar panels of 2.4 V and 80 mA, a voltage regulator element and rechargeable batteries. As a result, both in simulation and measurement, the mixed configuration (series-parallel) is the one that provides the best characteristics for its use, with a voltage of 4.57 V and a current of 127.3 mA, obtaining at the converter output a voltage of 19.44 V, concluding that the system meets the design expectations with which it was made, collecting energy, raising it and storing it, providing promising results for future applications.